Вертепна драма в сучасному студентському середовищі - Харчишин, О. (Народна творчість та етнографія, 2005)
Observation of emerging and spreading of vertep drama during the centuries is made by the author. Its regeneration in the first decades of the 20th century in the environment of student and youth societies is emphasized. The spread of "alive" form instead of the doll one is traced. Their compositional differences are investigated. The displays of key moments of compositional elements are distinguished: the sound of handbell, the scene with a shepherd, the scene with Herod, and main characters. Particular attention is paid to the texts, and their patriotic sense. Traditional and modificatory character features are traced in the article.